A pattern‐based risk‐stratification scheme for salivary gland cytology: A multi‐institutional, interobserver variability study to determine applicability. Issue 10 (21st August 2017) - Griffith, Christopher C.; Schmitt, Alessandra C.; Pantanowitz, Liron; Monaco, Sara E.
Abstract : BACKGROUND: Salivary gland aspiration cytology is useful in the preoperative management of patients but remains challenging, because of the extensive morphologic overlap of some tumors limits the ability to always determine the presence of malignancy. In response to this challenge, there has been increasing drive to develop a risk‐based categorization scheme for salivary gland aspirates. Herein, the authors examine the interobserver variability of 1 such pattern and risk‐based system. METHODS: Select smears and cell‐block sections of 50 salivary gland aspirates from 2 large academic centers were digitally imaged. These scanned slides were independently and blindly reviewed by 4 cytopathologists, and each aspirate was assigned to 1 of the proposed pattern‐based categories if it was considered neoplastic by the observer. Interobserver agreement was scored and aggregated risks of malignancy were calculated for cases with available surgical follow‐up. RESULTS: In total, 42 samples (84%) were considered neoplastic by at least 2 observers and were scored for interobserver agreement: 10 of 42 (23.8%) had uniform agreement, 14 of 42 (33.3%) had majority agreement, and 5 of 42 (11.9%) had divided agreement. Only 9 of 42 samples (21.4%) had minimal agreement, and 4 of 42 (9.5%) had no agreement. Condensation of similar categories was able to improve interobserver agreement and still maintain stratified risk of malignancy. CONCLUSIONS: The proposed pattern‐based risk‐stratification scheme, which could be implemented with the forthcoming Milan System, has good overall interobserver agreement and successfully stratifies the risk of malignancy. Some simplification is possible to make the system easier to use and improve interobserver agreement while maintaining stratification of risk. Cancer Cytopathol 2017;125:776‐85 . © 2017 American Cancer Society . Abstract : A recently proposed pattern‐based risk‐stratification scheme for salivary gland aspiration cytology is described. The system demonstrates good interobserver variability and confirms its ability to stratify the risk of malignancy.